Combining extracellular matrix proteome and phosphoproteome of chickpea and meta‐analysis reveal novel proteoforms and evolutionary significance of clade‐specific wall‐associated events in plant - Kanika Narula; Arunima Sinha; Pooja Choudhary; Sudip Ghosh; Eman Elagamey; Archana Sharma; Atreyee Sengupta; Niranjan Chakraborty; Subhra Chakraborty (Plant Direct)
Abstract Extracellular matrix (ECM) plays central roles in cell architecture, innate defense and cell wall integrity (CWI) signaling. During transition to multicellularity, modular domain structures of ECM proteins and proteoforms have evolved due to continuous adaptation across taxonomic clades under different ecological niche. Although this incredible diversity has to some extent been investigated at protein level, extracellular phosphorylation events and molecular evolution of ECM proteoform families remains unexplored. We developed matrisome proteoform atlas in a grain legume, chickpea and performed meta‐analyses of 74 plant matrisomes. MS/MS analysis identified 1,424 proteins and 315 phosphoproteins involved in diverse functions. Cross‐species ECM protein network identified proteoforms associated with CWI maintenance system. Phylogenetic characterization of eighteen matrix protein families highlighted the role of taxon‐specific paralogs and orthologs. Novel information was acquired on gene expansion and loss, co‐divergence, sub functionalization and neofunctionalization during evolution. Modular networks of matrix protein families and hub proteins showed higher diversity across taxonomic clades than among organs. Furthermore, protein families differ in nonsynonymous to synonymous substitution rates. Our study pointed towards the matrix proteoform functionality, sequence divergence variation, interactions between wall remodelers and molecular evolution using a phylogenetic framework. This is the first report on comprehensive matrisome proteoform network illustrating presence of CWI signaling proteins in land plants.